Pengaruh Faktor Motivasi Dan Persepsi Pengunjung Terhadap Keputusan Pembelian Tiket Pada Konser Act: Sweet Mirage In Jakarta - Ulfi Maranisya; Adelin Vinico Yuanita (Journal of Student Research, 2024)
This research aims to explore the motivational factors and perceptions of visitors influencing ticket purchasing decisions for the music concert titled Act: Sweet Mirage In Jakarta, featuring the South Korean group TOMORROW X TOGETHER. The study involved a sample of 87 respondents and utilized a quantitative analysis research method with data collected through questionnaires. The multiple linear regression analysis results indicated a regression coefficient value of 0.222 for motivational factors, showing a positive and significant impact on purchasing decisions. Additionally, the regression coefficient value for visitor perception factors was 0.630, indicating a positive impact on purchasing decisions. Both variables collectively influence the ticket purchasing decision for the Act: Sweet Mirage In Jakarta concert, as evidenced by the computed F-value of 8.847, which exceeds the critical F-value of 3.11.